2013
DOI: 10.1186/1475-2859-12-98
|View full text |Cite
|
Sign up to set email alerts
|

Non-recombinant display of the B subunit of the heat labile toxin of Escherichia coli on wild type and mutant spores of Bacillus subtilis

Abstract: BackgroundMucosal infections are a major global health problem and it is generally accepted that mucosal vaccination strategies, able to block infection at their entry site, would be preferable with respect to other prevention approaches. However, there are still relatively few mucosal vaccines available, mainly because of the lack of efficient delivery systems and of mucosal adjuvants. Recombinant bacterial spores displaying a heterologous antigen have been shown to induce protective immune responses and, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 32 publications
5
61
0
Order By: Relevance
“…Spores of B subtilis efficiently adsorb heterologous proteins, and adsorption is not dependent on specific spore surface molecules but rather on the negatively charged and hydrophobic surface of the spore (35,36). We have previously shown that in the adsorption of the ␤-galactosidase of Alicyclobacillus acidocaldaricus, the electrostatic interactions do not play a major role (20).…”
Section: Resultsmentioning
confidence: 99%
“…Spores of B subtilis efficiently adsorb heterologous proteins, and adsorption is not dependent on specific spore surface molecules but rather on the negatively charged and hydrophobic surface of the spore (35,36). We have previously shown that in the adsorption of the ␤-galactosidase of Alicyclobacillus acidocaldaricus, the electrostatic interactions do not play a major role (20).…”
Section: Resultsmentioning
confidence: 99%
“…D) At the end of sporulation the mother cell lyses releasing the mature spore with the antigen stably anchored to its surface. a dose of 2 × 10 9 spores, were displayed by the recombinant approach (CotC-LTB), while the same number of spores was able to display up to 5.5 μg of LTB by the nonrecombinant approach [37]. The 25-fold higher efficiency of display obtained with the non-recombinant strategy than with the recombinant one was further improved using mutant spores with an altered outer coat (cotH mutant spores).…”
Section: Recombinant Vs Non-recombinant Spore-surface Displaymentioning
confidence: 79%
“…LTB displayed by both strategies was able to induce a specific immune response in mucosally immunized mice [37,38]. An average of 9.6 × 10 -5 pg of LTB/spore, corresponding to approx.…”
Section: Recombinant Vs Non-recombinant Spore-surface Displaymentioning
confidence: 99%
See 2 more Smart Citations